1999
DOI: 10.1021/jp991797n
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study of the Structure and Thermochemistry of 1,3-Butadiene on the Ge/Si(100)-2 × 1 Surface

Abstract: We present an ab initio investigation of the structure and thermochemistry of the products of the chemisorption of 1,3-butadiene on the Ge/Si(100)-2 × 1 surface. The surface was modeled using a Si cluster with one dimer and Ge substitution for surface Si to study the effects of Ge on the cycloaddition. Calculations were performed using the Becke3LYP hybrid density functional theory method. Both the [4 + 2] Diels-Alder and the [2 + 2] cycloaddition products are energetically stable on all the Ge/Si(100)-2 × 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 51 publications
6
64
0
Order By: Relevance
“…This weaker binding of cyclopentene on Ge͑001͒ is consistent with other hydrocarbon cases such as ethylene, 20 benzene, 19 and 1,3-butadiene. 18 In contrast, a recent cluster calculation carried out by Lee et al 17 found that adsorbed cyclopentene on Ge͑001͒ has a relatively larger adsorption energy of 2.10 eV compared to that (E ads ϭ1.65 eV) on Si͑001͒. For the cyclopentene/Si͑001͒ system the adsorption energy obtained from the cluster calculation 17 agrees well with our value of 1.63 eV ͑for ϭ0.5 ML).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This weaker binding of cyclopentene on Ge͑001͒ is consistent with other hydrocarbon cases such as ethylene, 20 benzene, 19 and 1,3-butadiene. 18 In contrast, a recent cluster calculation carried out by Lee et al 17 found that adsorbed cyclopentene on Ge͑001͒ has a relatively larger adsorption energy of 2.10 eV compared to that (E ads ϭ1.65 eV) on Si͑001͒. For the cyclopentene/Si͑001͒ system the adsorption energy obtained from the cluster calculation 17 agrees well with our value of 1.63 eV ͑for ϭ0.5 ML).…”
supporting
confidence: 85%
“…[1][2][3][4] Especially the Si͑001͒ surface has been extensively employed for the investigation of hybrid organicsilicon systems, [5][6][7][8][9][10][11][12][13][14][15][16] whereas only little work addressed hydrocarbon adsorbates on the Ge͑001͒ surface. [17][18][19][20] There is a general consensus that the reaction of unsaturated hydrocarbons ͑e.g., alkenes͒ with Si͑001͒ takes place via a precursor state, finally forming a ͓2ϩ2͔ product in which the bond of alkene and the bond of a surface dimer interact to produce two bonds. 8,10,13,14 Although the reaction mechanisms of unsaturated hydrocarbons on Si͑001͒ and Ge͑001͒ are expected to be similar to each other because of the same surface reconstruction, it is interesting to point out that there is a chemically subtle difference in the adsorption kinetics on the two surfaces.…”
mentioning
confidence: 99%
“…Furthermore, the weak π-bond between the two surface dimer atoms makes the dimer appear as a reactive olefin that is active toward olefinic reactions, such as cycloadditions. 10,11 Although alanine and arginine play important roles in the chemistry of proteins, we here examine their reactivity on the Ge(100)-2×1 surface as multifunctional organic molecules ( Figure 1). However, these results also serve as a basis for how these individual amino acids would interact with the Ge(100)-2×1 surface as part of a polypeptide.…”
Section: Introductionmentioning
confidence: 99%
“…The dangling bonds of Si(100) and Ge(100) surfaces are arranged in surface dimers which consist of a strong σ bond and a weak π bond. The π-bond strength has been reported to be 2-10 kcal/ mol, [13][14][15][16][17] much less than the 65 kcal/mol of alkene, 18 in which the weak π bond allows the surface dimers of Si(100) and Ge-(100) to be highly reactive. Due to electronic effects of solid state, the partially π-bonded surface dimers tilt out and thus the distortion induces the charge transfer from the "down" (electrophile) to the "up" (nucleophile) surface atom.…”
Section: Introductionmentioning
confidence: 99%